Study of Numerical Schemes for the CFD Simulation of Human Airways - Kumar, Bholu; Srivastav, Vivek Kumar; Jain, Anuj; Paul, Akshoy Ranjan (International Journal of Integrated Engineering, 2019)
Computational fluid dynamics (CFD) is increasingly used nowadays to capture air and particle transport in human respiratory tract model. In the present study, computer tomography (CT) scan based respiratory tract model is used for the CFD simulation. The main objective of the present study is to compare different pressure-velocity schemes (SIMPLE, SIMPLEC, PISO and COUPLED schemes) in terms of convergence and computational time. Numerical simulation is done for three inhalation flow rates, namely 20, 40 and 60 liters per minute for predictions of flow phenomena inside the sixth generation human airways and also to predict the effects of flow parameters; pressures and velocity on the sixth generation Human Airways. Low Reynolds Number (LNR) k-Ï‰ model is used to capture the turbulence effect. The findings will be useful for medical practitioner to understand complex airflow patterns in the human airways. Also, pressure distribution and velocity distribution help to define the medical phenomena in core engineering terms.